Military Slangs and Their Semantic Features - o’g’li, Xoshimov Lutfullo Xabibullo (Research Parks Publishing LLC, 2023)
The main purpose of this article is to ascertain how military slang terms are formed and how they can be obtained by English learners in the process of evolving their language and development among advanced learners. Types of slang that can be found in everyday life were recognized and examined, including one of the main ones.